3D Printing of Biomass-Fungi Composite Material: A Preliminary Study. (April 2020) - Bhardwaj, Abhinav; Vasselli, Joseph; Lucht, Matt; Pei, Zhijian; Shaw, Brian; Grasley, Zachary; Wei, Xingjian; Zou, Na
Abstract: This paper reports a 3D printing based manufacturing method using biomass-fungi composite material. The biomass is derived from waste agricultural materials. The fungi grow through the biomass and bind the biomass together. The novel method comprised the preparation of a printable biomass-fungi mixture. After printing, the fungi grew inside the printed sample over a few days. The feasibility of this new method was demonstrated by a preliminary experiment. In comparison to molding based manufacturing processes, 3D printing can facilitate greater flexibility in design and print custom designs for packaging and construction applications.